2011
DOI: 10.1111/j.1365-313x.2011.04572.x
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol kinase is involved in farnesol metabolism, ABA signaling and flower development in Arabidopsis

Abstract: SUMMARYFarnesol, which is toxic to plant cells at high concentrations, is sequentially phosphorylated to farnesyl phosphate and farnesyl diphosphate. However, the genes responsible for the sequential phosphorylation of farnesol have not been identified and the physiological role of farnesol phosphorylation has not been fully elucidated. To address these questions, we confirmed the presence of farnesol kinase activity in Arabidopsis (Arabidopsis thaliana) membranes and identified the corresponding gene (At5g585… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…At1g78620 is weakly related to phytol kinases from different organisms, including Arabidopsis (At5g04490/ VTE5, 17.5% identity). The phytol kinase/VTE5 sequences cluster into a cyanobacterial/plant group containing At5g04490 (VTE5) and a related sequence (At5g58560, VTE5-like) (Fitzpatrick et al, 2011) and the second branch containing the phytol kinase domains that form fusion proteins with COG1836 sequences from Chlorobi and Firmicutes (Supplemental Figure 1) (Valentin et al, 2006).…”
Section: The Cog1836 Sequence At1g78620 Shows Similarity With Cytidylmentioning
confidence: 99%
“…At1g78620 is weakly related to phytol kinases from different organisms, including Arabidopsis (At5g04490/ VTE5, 17.5% identity). The phytol kinase/VTE5 sequences cluster into a cyanobacterial/plant group containing At5g04490 (VTE5) and a related sequence (At5g58560, VTE5-like) (Fitzpatrick et al, 2011) and the second branch containing the phytol kinase domains that form fusion proteins with COG1836 sequences from Chlorobi and Firmicutes (Supplemental Figure 1) (Valentin et al, 2006).…”
Section: The Cog1836 Sequence At1g78620 Shows Similarity With Cytidylmentioning
confidence: 99%
“…In addition, folk flowers develop supernumerary carpels under water stress conditions. 6 From these observations, three hypotheses were developed:…”
mentioning
confidence: 99%
“…5 Farnesol kinase and farnesyl phosphate kinase activities were recently confirmed in Arabidopsis seedling membranes. 6 Interestingly, CTP, ATP, GTP and UTP served as phosphoryl donors for conversion of [ Plant responses to abiotic stress are regulated by a multitude of hormone signals, transcription factors, microRNAs and ion channels. [7][8][9][10] Drought responses, for example, are mediated in part by the sesquiterpene phytohormone abscisic acid (ABA) and many genes have been identified that influence, or are influenced by, ABA signaling.…”
mentioning
confidence: 99%
“…This lipid, farnesol, can then undergo two steps of phosphorylation, creating the phosphorylated lipid farnesyl monophosphate (FP) after the first phosphorylation and farnesyl diphosphate (FPP) following the second phosphorylation (Fitzpatrick, Bhandari, & Crowell, 2011;Hemmerlin & Bach, 2000;Hemmerlin et al, 2006). The enzyme used to mediate the second step of this phosphorylation process is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme used to mediate the second step of this phosphorylation process is still unknown. The FOLK gene was recently found to code for the enzyme, farnesyl kinase, used to mediate the phosphorelation of farnesyl to farnesyl monophosphate but not farnesyl monophosphate to farnesyl diphosphate (Fitzpatrick et al, 2011). After the conversion of FP to FPP, the fate of the farnesyl diphosphate is then protein prenylation, to attach the diphosphate lipid to a protein using the enzyme protein farnesyltransferase (PFT) (Crowell & Huizinga, 2009;Zhang & Casey, 1996).…”
Section: Introductionmentioning
confidence: 99%